2011
DOI: 10.1590/s1806-83242011000500014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tetracycline on the bond performance of etch-and-rinse adhesives to dentin

Abstract: This study evaluated the effect of modified tetracycline on the resin-dentin bond strength (µTBS), silver nitrate uptake (SNU) and solution homogeneity (SH) of two adhesives. Dentin surfaces were treated with phosphoric acid, rinsed off and either rewetted with water (control group -CO), 2% minocycline (MI), 2% doxycyline (DO) or 2% chlorhexidine (CH). Adhesive systems (Adper Single Bond 2 and Prime Bond NT) and composite were applied and light-polymerized. Specimens were sectioned to obtain bonded sticks (0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
(32 reference statements)
2
9
0
Order By: Relevance
“…101 Bisphosphonates, such as batimastat, galardin, and zoledronate, also inhibit MMPs by chelating active-site zinc, and zoledronate inhibits carious dentin MMPs.…”
Section: Enzyme Inhibitorsmentioning
confidence: 99%
“…101 Bisphosphonates, such as batimastat, galardin, and zoledronate, also inhibit MMPs by chelating active-site zinc, and zoledronate inhibits carious dentin MMPs.…”
Section: Enzyme Inhibitorsmentioning
confidence: 99%
“…Although the application of aqueous solutions of minocycline and doxycycline as a preliminary step after acid‐etching on the immediate bonding performance was recently investigated, the use of TCs and their analogues in dentin bonding as a way to prolong resin–dentin bonds is still scarce in the literature and should be the focus of further investigation because of the potential role of TCs on MMP inhibition.…”
Section: Inhibitors Of Proteolytic/collagenolytic Activitymentioning
confidence: 99%
“…Doxycycline is safer than minocycline and is one of the common antimicrobial TCs studied as an anticancer agent [129][130][131] and as adjunctive treatment for the management of chronic periodontitis. 132,133 Although the application of aqueous solutions of minocycline and doxycycline as a preliminary step after acid-etching on the immediate bonding performance was recently investigated, 134 the use of TCs and their analogues in dentin bonding as a way to prolong resin-dentin bonds is still scarce in the literature and should be the focus of further investigation because of the potential role of TCs on MMP inhibition.…”
Section: Tetracyclines and Analoguesmentioning
confidence: 99%
“…However, in some other studies, doxycycline negatively affected the bonding of the etch-and-rinse adhesive [28,29]. The increased depth of demineralization which was not compatible with the depth of resin monomer infiltration in the study by Elkassas et al [28] and phase separation observed for doxcycycline after mixing with bonding agents in the study by Stanislawczuk et al [29], resulted in lower shear bond strength values observed.…”
Section: Microscopic Analysismentioning
confidence: 88%